Necesidades de capacitación al docente en el manejo de las tecnologías de información y comunicación en los procesos formativos de los estudiantes de la parroquia Aláquez en el período Septiembre 2012 - Julio 2013. Propuesta de estrategias para mejorar la utilización de las TICS. - Cóndor Mallitásig, Cristian Vicente (2013)
The Information and Communication Technologies (TICS) now constitute an important resource for improving the performance of teachers in academic activities and in particular it has proven to be an effective means of teaching support. The general objective of this researching is to develop a diagnostic on the use of tics by teachers in the teaching- learning process of the students in Aláquez parish schools. The results of this researching show that there is a set of problems that are currently limiting the use of these tools by teachers in Aláquez parish schools. among the problems are identified , inadequate teacher training ,they do not prioritized the use of computing resources in schools , also the participation, incentive and motivation , are weakness, and the absence of use of tics by teachers is the first aspect that really showed in the researching process . Also it has made a set of strategies for solving this problem and improving the performance of teachers in the classroom. these strategias should include the following: sensitivity and awareness to teachers through seminars on the use of tics and the potential that they offers , developing a training manual for teachers in Aláquez parish schools to use these tools in the teaching-learning process, in order to get a better performance of teachers in academic activities.